2019
DOI: 10.1039/c9ta01598a
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-deficient titanium dioxide as a functional host for lithium–sulfur batteries

Abstract: Engineering oxygen vacancies in mesoporous TiO2 effectively enhanced its ability to trap polysulfides and simultaneously propelled the redox conversion of polysulfides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
68
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(69 citation statements)
references
References 73 publications
0
68
1
Order By: Relevance
“…When metal compounds such as TiO 2 and MoS 2 as sulfur hosts contain the vacancies, their electrons below the Fermi level can leap into the defect level, which would create a hole carrier and lower the barrier of electron transition to the conduction band, resulting in the improvement of the electronic conductivity and the acceleration of the lithium polysulfides (LiPSs) conversion reaction kinetics. [28] Vacancies can form the electron-rich region and abundant active sites, enhancing Li-ion storage performance and inhibiting the diffusion and shuttle of active materials. For some sulfur hosts, the vacancy defects possessing the abundant localized electron would act as active centers for the adsorption, which could generate stronger adsorption strength for LiPSs than the bonding energy with dioxolane/dimethoxyethane (DOL/DME), thus the presence of vacancies in sulfur hosts can effectively inhibit the diffusion and shuttle of LiPSs, leading to the enhancement in electrochemical performance of LiÀ S batteries.…”
Section: Vacanciesmentioning
confidence: 99%
“…When metal compounds such as TiO 2 and MoS 2 as sulfur hosts contain the vacancies, their electrons below the Fermi level can leap into the defect level, which would create a hole carrier and lower the barrier of electron transition to the conduction band, resulting in the improvement of the electronic conductivity and the acceleration of the lithium polysulfides (LiPSs) conversion reaction kinetics. [28] Vacancies can form the electron-rich region and abundant active sites, enhancing Li-ion storage performance and inhibiting the diffusion and shuttle of active materials. For some sulfur hosts, the vacancy defects possessing the abundant localized electron would act as active centers for the adsorption, which could generate stronger adsorption strength for LiPSs than the bonding energy with dioxolane/dimethoxyethane (DOL/DME), thus the presence of vacancies in sulfur hosts can effectively inhibit the diffusion and shuttle of LiPSs, leading to the enhancement in electrochemical performance of LiÀ S batteries.…”
Section: Vacanciesmentioning
confidence: 99%
“…However, Fe 2 O 3 , just like most of other metal oxides, yields intrinsically low conductivity, which prevents from making full use of the advantage of itself. [ 26 ] Interestingly, it is demonstrated that the conductivity of metal oxides can be effectively improved through implanting oxygen‐deficient structure. In addition, surface defects could enhance the catalytic activity of catalysts through tuning their electronic structures.…”
Section: Introductionmentioning
confidence: 99%
“…The growing requirements of sustainable and green energy are promoting the practical applications of energy storage devices. Batteries have been broadly applied for communication devices and new energy vehicles because of the environmental friendliness and high energy density . For lithium ion batteries (LIBs), the tremendous demand for lithium results in its unavailability .…”
Section: Introductionmentioning
confidence: 99%